Implementasi Peraturan Bupati Gayo Lues Nomor 14 Tahun 2014 Tentang Pajak Bumi Dan Bangunan Perkotaan Dan Pedesaan - Alfi Husni; Isnaini Isnaini; Adam Adam (PERSPEKTIF, 2022)
This study aims to analyze how the implementation of the Gayo Lues Regent’s Regulation Number 14 of 2014 concerning urban and rural land and building taxes in Gayo Lues District and to find out the obstacles in the implementation of the Gayo Lues Regent’s regulation number 14 of 2014 concerning urban and rural land and building taxes in Gyao Lues district. The research method used in this research is descriptive with qualitative analysis. Data collection was obtained from interviews, observations and documentation. The Research results were tasted using George Edward III’s theory, wich consisted of (1). Communication, (2). Resources, (3). Bereaucratic Structure and (4). Dispotition. The results of this study indicate that the implementation og Gayo Lues Regent’s Regulation Number 14 of 2014 concerning Urban and Urban Land and Building Taxes in Gayo Lues District has been implemented but has not given optimal result, because it faces several obstacles, including the lack of diect socializatation of land and building taxes to the community, limited human resources in terms of quantity and competence possessed. limited facilities to support activities, lack of budget to support the implementation of activities.